A CONCEPTUAL RESEARCH ON PERCEIVED VICTIMIZATION, ORGANIZATIONAL REVENGE INTENTION AND FORGIVENESS TENDENCY (Third Sector Social Economic Review, 2019)
Offensive, damaging and unfair behaviors that employees encounter or suffer in the workplace are an important problem that threatens the working life and needs to be solved. Therefore, with the recent rise in research on such behaviors, these behaviors have become the focus of disciplines such as management psychology.The aim of this study is to examine theoretically the aggressive behavior and the victimisation resulting from violence in organizations towards forgiveness tendency and revenge intention. Literature review was used as the method in the study. In the study, primarily aggressive behaviors in organizations have been mentioned. Subsequently, victimization as a result of aggressive behaviors and behaviors such as forgiveness tendency and revenge intention experienced by the individual as a result of victimization were examined. Finally, the relations between these concepts have been revealed. In the literature review, it was concluded that eliminating the problems among the employees, preventing the victimization and consequent intention of revenge, and ensuring the reconciliation, forgiveness and peace are among the priority tasks of the administration.
Keywords: Perceived Victimization; Revenge Intention; Forgiveness Tendency